Primary and Secondary Prevention of Obesity - Kiełczewska, Aleksandra; Szcześniak, Grzegorz; Kiełczewska, Anna (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Obesity is a persistent and recurring chronic condition marked by an excessive accumulation of body fat, which can deteriorate health, heighten the risk of complications, and shorten life expectancy.This review provides a comprehensive overview of the primary and secondary prevention of obesity, with a focus on interventions and strategies. Material and methods: An extensive examination of articles published in scientific journals was carried out through online research platforms PubMed and Google Scholar. We searched articles by entering keywords in appropriate configuration: “primary prevention of obesity”, “secondary prevention of obesity”, “obesity”. Description of the state of knowledge: According to published data, the growing problem of obesity translates into negative consequences in the form of the development of numerous complications associated with it and a shortening of the life expectancy of patients. Primary prevention of obesity includes health policy and health care that aim to prevent the development of obesity. Secondary prevention focuses on detecting and treating obesity at an early stage to prevent the development of complications. Summary: Implementing comprehensive primary prevention strategies across the population could substantially decrease the occurrence of numerous chronic conditions associated with overweight and obesity, yet effective large-scale programs to achieve this are currently lacking.